Interleukin 2 in Cancer Therapy - K. Antony, G.; Z. Dudek, A. (Current Medicinal Chemistry, 2010)
Cancer immunotherapy with interleukin-2 (IL-2) has demonstrated long term disease control in metastatic renal cell carcinoma and malignant melanoma. With introduction of novel kinase inhibitors, immunomodulatory molecules, cytokines, and vaccines for treatment of cancer there is an increased interest in combining these therapeutic strategies with IL-2. Here we discuss toxicity and established activity of IL-2 in the management of advanced malignancies, and speculate on future use of this cytokine for treatment of cancer.
Keywords: Interleukin-2